Goldfrank's toxicologic emergencies - Nelson, Lewis 1963-; Smith, Silas W.; Hoffman, Robert S.; Howland, Mary Ann; Goldfrank, Lewis R.; Lewin, Neal A.; Flomenbaum, Neal E. (McGraw-Hill Education, 2019)
"Goldfrank's Toxicological Emergencies is a multi-authored text of more than 2000 pages prepared by utilizing the education and management principles we apply at the New York City Poison Center and at our clinical sites. In this ninth edition of Goldfrank's Toxicological Emergencies, we proudly offer readers an approach to medical toxicology using evidence based principles viewed through a lens of bedside clinical practice" -- Provided by publisher.